Jehanne D'Arc and claims to divine sanction in acts of war : a double-edged sword - Novack, Brenda Elizabeth (Irish School of Ecumenics, 2013)
This work conducts a theological exploration and interpretation of the heavily documented life and death of Saint Jehanne d'Arc (Joan of Arc) in the context of claims to divinely sanctioned violence, particularly within the sphere of war. Primary materials pertaining to Jehanne, including trial transcripts, correspondence, and contemporary chronicles, form the main research base, and this is supplemented with a diverse selection of theological and historical secondary sources demonstrating Jehanne's broad relevance.
Keywords: Religions, Theology and Ecumenics, Ph.D.; Ph.D. Trinity College Dublin.